ETHICS AND BUSINESS IN SPORT-CONTRIBUTION OF SOCIAL RESPONSIBLE BUSINESS STRATEGY - Vladimir Marinković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
History of human society confirm that responsibility is one of basic principles, of key importance in all ages, an all forms of political and economic organisation of society. Also, in history, and contemporary age we can find different understanding and definitions of responsibility, dependentlly of social circumstances, or social position of some social groups or individuals. Very important role in the frame of social responsible business isssue have be a sport whose development is one of the main pillars of alla of society. From that reason, in accordance with globalisation process, sport became to pic of interesto of international organisations which define rools and standards which is important for sport development in each country in the world. Hovewer, in contemporary society is visible there is direct proportion between level of resposibility and level of democracy, human rights and freedoms, economic developement and quallity of life Social responsible bussines, may be defined as collection of principles which oblige participants of economic life to take care not only about individual interests, bal also about interests of society in whole. In other words, social responsible bussines is applied etic in the field of economy, first of all in managing with capital and human resources.In that poent of view, social responsible bussines is esentially conected with other civilisation approaches - freedom,equallity, social justice.